Performance of fluorescent europium(III) nanoparticles and colloidal gold reporters in lateral flow bioaffinity assay - Juntunen E; Myyrylainen T; Salminen T; Soukka T; Pettersson K (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2025)
Lateral flow (LF) immunoassays (i.e., immunochromatographic assays) have traditionally been applied to analytes that do not require very high analytical sensitivity or quantitative results. The selection of potential analytes is often limited by the performance characteristics of the assay technology. Analytes with more demanding sensitivity requirements call for reporter systems enabling high analytical sensitivity. In this study, we systematically compared the performance of fluorescent europium(III) [Eu(III)] chelate dyed polystyrene nanoparticles and colloidal gold particles in lateral flow assays. The effect of time-resolved measurement mode was also studied. Because binder molecules used in immunoassays might not behave similarly when conjugated to different reporter particles, two model assays were constructed to provide reliable technical comparison of the two reporter systems. The comparative experiment demonstrated that the fluorescent nanoparticles yielded 7- and 300-fold better sensitivity compared with colloidal gold in the two test systems, respectively. Although the two reporter particles may induce variable effects using individual binders, overall the high specific activity of Eu(III) nanoparticles has superior potential over colloidal gold particles for the development of robust high-sensitivity bioaffinity assays. (C) 2012 Elsevier Inc. All rights reserved.